Political Realism of Gonzalo Fernández de La Mora. (2007)
Gonzalo Fernandez De La Mora (1924-2002), spanish philosopher and jurist belongs to one of those generations really fundamental in Spain’s XX Century. Student and fellow scholar of the great political jurists of the epoch (such as Javier Conde, Luis Diez